Solution Structure of Inhibitor-Free Human Metalloelastase (MMP-12) Indicates an Internal Conformational Adjustment - Bhaskaran, Rajagopalan (2007)
Macrophage metalloelastase or MMP-12 appears to exacerbate atherosclerosis, emphysema, aortic aneurysm, rheumatoid arthritis, and inflammatory bowel disease. An inactivating E219A mutation, validated by crystallography and NMR spectra, prevents autolysis of MMP-12 and allowed us to determine its NMR structure without an inhibitor. The structural ensemble of the catalytic domain without inhibitor is based on 2813 NOEs and has an average RMSD to the mean of 0.25 Å for the backbone and 0.61 Å for all heavy atoms for residues Trp109 - Gly263. Compared to crystal structures of MMP-12, helix B (hB) at the active site is unexpectedly more deeply recessed under the beta-sheet. This opens a pocket between hB and β-strand sIV in the active site cleft. Both hB and an internal cavity are shifted toward β-strands sI and sIII and hA on the back side of the protease. About 25 internal NOE contacts distinguish the inhibitor-free solution structure and indicate hB’s greater depth and proximity to the sheet and hA. Line broadening and multiplicity of amide proton NMR peaks from hB are consistent with hB undergoing slow conformational exchange among subtly different environments. Inhibitor binding-induced perturbations of NMR spectra of MMP-1 and -3 map to similar locations across MMP-12 and encompassing its internal conformational adjustments. Evolutionary trace analysis suggests a functionally important network of residues that encompasses most of the locations that adjust in conformation, including 18 residues with NOE contacts unique to inhibitor-free MMP-12. The conformational change, sequence analysis, and inhibitor perturbations of NMR spectra agree in the network they identify between structural scaffold and active site of MMPs.